Sexting and revenge pornography : legislative and social dimensions of a modern digital phenomenon - Phippen, Andy (Routledge, 2021)
This book considers the rapidly evolving, both legally and socially, nature of image-based abuse, for both minors and adults. Drawing mainly from UK data, legislation and case studies, it presents a thesis that the law is, at best, struggling to keep up with some fundamental issues around image based abuse, such as the sexual nature of the crimes and the long term impact on victims, and at worst, in the case of supporting minors, not fit for purpose. It shows, through empirical and legislative analysis, that the dearth of education around this topic, coupled with cultural norms, creates a victim blaming culture that extends into adulthood. It proposes both legislative developments and need for wider stakeholder engagement to understand and support victims, and the impact the non-consensual sharing of intimate images can have on their long-term mental health and life in general. The book is of interest to scholar of law, criminology, sociology, police and socio-technical studies, and is also to those who practice law, law enforcement or wider social care role in both child and adult safeguarding.